PENGARUH EFEKTIVITAS PENGGUNAAN GOOGLE CLASSROOM TERHADAP KEPUASAN MAHASISWA PADA MATA KULIAH KEWIRAUSAHAAN - Defri Triadi (PENDIDIKAN SAINS DAN TEKNOLOGI, 2022)
This study aims to determine the effectiveness of using google classroom, find out the level of student satisfaction using google classroom, and find out the effect of the effectiveness of using google classroom on student satisfaction in entrepreneurship courses. This research method is a quantitative method. The object of this study is a 6th semester student of IAKN Palangka Raya. The research sample of students who took entrepreneurship courses totaled 123 students. Data collection by spreading questionnaires was analyzed with simple linear regression analysis techniques. Conclusion: 1) The effectiveness of using google classroom is in the high category, but there are findings that some students are not used to using google classroom. 2) Student satisfaction with the use of google classroom is in the high category, but there are findings that some students who have difficulty understanding the lecture material, some students are dissatisfied with the appearance of google classroom which is difficult to understand and have difficulty obtaining feedback on the assignments done. 3) There is a significant influence on the effectiveness of using google classroom on student satisfaction.